Does Yahweh exist? A philosophical-critical reconstruction of the case against realism in Old Testament theology - Gericke, Jaco (Old Testament essays, 2004)
In this article the question is asked whether Yahweh as depicted in the texts of the Old Testament really exists or whether the deity might actually be a character of fiction with no counterpart outside the worlds of text and imagination. Though rather unheard of as a research problem, and almost impossible to deal with in any interpretative methodology currently operative, the interrogative concerning the ontological status of Yahweh can be approached meaningfully by utilising philosophy of religion as an auxiliary discipline within Old Testament studies. In doing so, the hypothesis this paper intends to argue in favour of is that Yahweh as depicted in the Old Testament texts does not exist. In justification of such a controversial claim, seven arguments against the existence of Yahweh have been reconstructed based on the perceived anti-realist ontological implications of theological pluralism, unorthodox theology, polymorphic projection, mythology / syncretism, fictitious cosmography and fictitious history in the texts. The result is a cumulative case against realism in Old Testament theology which, if consistently applied, also leads to the collapse of realism in any theology that is in any way rooted in, derived from, or based on the discourse of Old Testament Yahwism.